Ischemic heart disease cause of intradialytic hypertension in a patient with diabetic nephropathy. Issue 4 (October 2020) - Uchida, Masato; Kawano, Hiroaki; Koga, Seiji; Ikeda, Satoshi; Eishi, Kiyoyuki; Maemura, Koji
Abstract: A 73-year-old Japanese man was admitted with extreme intradialytic hypertension of four months' duration that was refractory to antihypertensive agents. He had started hemodialysis five years previously because of diabetic nephropathy. Coronary angiography revealed coronary artery disease with significant stenosis of the left main trunk and the right coronary artery, and he underwent a coronary artery bypass graft. Thereafter, the intradialytic hypertension disappeared. Ischemic heart disease appears to be one cause of intradialytic hypertension. <Learning objective: Intradialytic hypertension occurs in some patients with hemodialysis. Such patients are at increased risk for mortality and adverse cardiovascular events. Although the pathophysiological mechanisms remain unknown, ischemic heart disease appears to be one cause of intradialytic hypertension.>